2017
DOI: 10.4085/1062-6050-52.11.18
|View full text |Cite
|
Sign up to set email alerts
|

Hip Strength as a Predictor of Ankle Sprains in Male Soccer Players: A Prospective Study

Abstract: Reduced isometric hip-abductor strength predisposed competitive male soccer players to noncontact lateral ankle sprains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 44 publications
2
36
1
1
Order By: Relevance
“…Although sagittal plane pelvic deviation was not found being a significant risk factor for lower extremity injuries, the relationship between excessive pelvic tilt and low‐back injuries should be investigated more thoroughly in future studies. Impaired hip strength has been suggested to also increase the risk of ankle injuries, but in our study, we did not observe association between pelvic control and ankle injury risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sagittal plane pelvic deviation was not found being a significant risk factor for lower extremity injuries, the relationship between excessive pelvic tilt and low‐back injuries should be investigated more thoroughly in future studies. Impaired hip strength has been suggested to also increase the risk of ankle injuries, but in our study, we did not observe association between pelvic control and ankle injury risk.…”
Section: Discussionmentioning
confidence: 99%
“…20 This study showed that decreased anterior-posterior control of the pelvis among baseball pitchers is related to long time loss due to injuries but did not differentiate between injured body parts. 20 Furthermore, impaired hip strength has been suggested to increase the risk of ankle injuries, 21 but prospective studies are scarce, and results have been partly conflicting. 22 More studies are needed to determine the role of hip and pelvic control to the risk of LE injuries, especially to the knee and ankle.…”
mentioning
confidence: 99%
“…These factors withstanding, study findings based on kinematic and subject perception data provide encouraging results. Non-contact knee injuries in all athletes, but particularly among females are known to be associated with excessive, or poorly controlled frontal plane knee motion (1,3,4,45). Although compression garment use above the knee has not been found to improve proprioception through dynamometer target angle position tests, these findings likely differ considerably from the knee joint neuromuscular control demands associated with functional movements (46).…”
Section: Limitationsmentioning
confidence: 99%
“…Poorly controlled dynamic knee valgus (frontal plane knee motion) during activities greatly increases non-contact knee injury risk, particularly among athletic girls and women (1)(2)(3). The combination of poorly controlled, hip adduction-internal rotation and knee abduction that occurs with the sudden single leg loading of many athletic maneuvers can transmit injurious loads to the medial collateral ligament, medial meniscus, and anterior cruciate ligament and may also contribute to lateral patello-femoral joint disloca-tion (1)(2)(3). Previous studies have evaluated how knee brace or sleeve use can help prevent knee injury (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Increased peak knee abduction angles (also known as knee valgus position) has been identified as a common predisposition to noncontact anterior cruciate ligament injury, patellofemoral pain, medial tibial stress syndrome, chronic ankle instability, and noncontact ankle sprains. [1][2][3][4][5][6][7][8][9][10][11] Weak hip external rotator and abductors are hypothesized to increase hip internal rotation and adduction, which increases peak knee abduction angles during running and landing. 1,[7][8][9][10][12][13][14][15][16][17] For this reason, recent research has focused on identifying relationships between hip strength (i.e.…”
Section: Introductionmentioning
confidence: 99%